Editor’s Note. - Alonso Betanzos, Amparo; Cabalar, Pedro; P. Dimuro, Gracaliz; García, Marcos; Hernández Orallo, José; Hervás, Raquel; Manjarés, Ángeles; Martínez Plumed, Fernando; Mora Jiménez, Inmaculada; Sànchez Marré, Miquel (International Journal of Interactive Multimedia and Artificial Intelligence, 2021)
Artificial Intelligence has become nowadays one of the main relevant technologies that is driven us to a new revolution, a change in society, just as well as other human inventions, such as navigation, steam machines, or electricity did in our past. There are several ways in which AI might be developed, and the European Union has chosen a path, a way to transit through this revolution, in which Artificial Intelligence will be a tool at the service of Humanity. That was precisely the motto of the 2020 European Conference on Artificial Intelligence (“Paving the way towards Human-Centric AI”), of which these special issue is a selection of the best papers selected by the organizers of some of the Workshops in ECAI 2020.